MEMBINA AKHLAK ANAK USIA DINI DALAM PENDIDIKAN RELIGIUS DI ERA DIGITAL - Cahaya Cahaya (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2023)
Digitalization has an impact on all aspects of human life, changes in mindset and lifestyle are unavoidable. One problem that is very worrying is the emergence of various kinds of social media that can damage morals. Moral education is very important and must be carried out from an early age, before their character and personality are affected by the environment. Parents' parenting styles at home and educators at school will influence the emotional, behavioral, social-cognitive development, and health of children's psychological functioning into adulthood. Moral education with the right method is the main key so that children are able to control themselves in using digital media and can take advantage of technological and communication sophistication for things that are useful for them. The methods in moral education that can be applied in today's digital era include; exemplary methods, habituation, advice, attention, humor and supervision